Elevated Serum C1q Levels in Children With Sepsis - Li, Huan; Chen, Juanjuan; Hu, Yuanhui; Cai, Xin; Zhang, Pingan (Frontiers in Pediatrics, 2021)
Objective: To analyze the serum complement C1q levels in children with sepsis, and explore the suggestive effect of serum C1q levels on the condition of children with sepsis. Methods: The clinical and laboratory data of children with sepsis (n = 95) and healthy children (n = 71) in Renmin Hospital of Wuhan University from January 2019 to October 2019 were collected, and each index of the two groups was compared. Then we divided children with sepsis into three subgroups based on the Pediatric Critical Illness Score (PCIS): non-critical group, critical group, and extremely critical group. The serum C1q and PCT levels of the three subgroups were analyzed, and the correlation analysis was carried out between the levels of serum C1q and PCT levels as well as PCIS among children with sepsis. Finally, we analyzed the serum C1q levels of septic children infected by different pathogens. Results: The serum C1q levels of children with sepsis were significantly higher than those of healthy children (median 198.4 vs. 186.2 mg/L, P < 0.001). In the analysis of subgroups, the serum C1q levels of non-critical group, critical group, and extremely critical group septic children were 182.80 (166.75, 195.85) mg/L, 219.90 (209.10, 246.40) mg/L and 249.95 (239.10, 272.25) mg/L respectively, which were correlated with the severity of the disease. At the same time, we also found that serum C1q in children with sepsis was positively correlated with PCT levels (r = 0.5982, P < 0.001), and negatively correlated with PCIS score (r = -0.6607, P < 0.001). The serum C1q levels of septic children with bacterial infections, mycoplasma infections, viral infections, and co-infection were higher than those of the control group (P < 0.05). Conclusion: The serum levels of C1q in children with sepsis were increased and related to the severity of sepsis, suggesting that C1q may be involved in the occurrence and development of sepsis, which had reference value for the preliminary diagnosis and severity classification of sepsis.